2019
DOI: 10.1021/acscatal.9b00852
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Speciation of Cu in the Cu-H-Mordenite Catalyst for the Oxidation of Methane to Methanol

Abstract: The proton form of Cu-exchanged mordenite (Cu-H-MOR) was prepared via ion-exchange, and the nature of the active Cu species in the cyclic oxidation of CH 4 to CH 3 OH was investigated by high-pressure reactivity testing, X-ray absorption spectroscopy (XAS), and H 2 temperature-programmed reduction (TPR). Increasing the CH 4 pressure from 1 to 35 bar and the reaction time from 4 to 20 h increased the product yield from 0.30 to 0.42 mol (mol Cu) −1 , suggesting that at lower pressures and shorter reaction times,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
123
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(132 citation statements)
references
References 74 publications
8
123
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Furthermore, a propensity for Cu II to be reduced to Cu I under the influence of X-ray beams has been demonstrated previously, and found to be a function of the nature of counter ions present in homogeneous (aqueous) systems. 13,19 However, and in spite of many previous X-ray spectroscopic studies of the behaviour of copper containing zeolites for the direct conversion of methane to methanol, 26,27,29,31,35,41,42,[45][46][47][48][49][50][51][52] we are unaware of any previous consideration that the results may have been influenced by the application of the X-ray probe. The results we have obtained show that some good degree of circumspection needs to be applied to the study of these types of material if one is to reliably access the chemistry intrinsic to the material.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Furthermore, a propensity for Cu II to be reduced to Cu I under the influence of X-ray beams has been demonstrated previously, and found to be a function of the nature of counter ions present in homogeneous (aqueous) systems. 13,19 However, and in spite of many previous X-ray spectroscopic studies of the behaviour of copper containing zeolites for the direct conversion of methane to methanol, 26,27,29,31,35,41,42,[45][46][47][48][49][50][51][52] we are unaware of any previous consideration that the results may have been influenced by the application of the X-ray probe. The results we have obtained show that some good degree of circumspection needs to be applied to the study of these types of material if one is to reliably access the chemistry intrinsic to the material.…”
Section: Discussionmentioning
confidence: 98%
“…44,[53][54][55] Copper containing zeolites have been the focus of much academic attention since the discovery in 2005 21,22 that, when hosted in certain zeolites, some of the Cu II species that result from activation at elevated temperatures can successfully mediate the selective conversion of methane conversion. Subsequent research has resulted in great improvements in performance, and synchrotronbased X-ray absorption spectroscopy (XAS) has often been employed to elucidate aspects of how the Cu II species supported upon amorphous oxides, 20 or contained within the microporous structure of the zeolites, 26,27,29,31,35,41,42,[45][46][47][48][49][50]52 facilitate the conversion of methane to methanol. Indeed, quantitative XAS measurements, when coupled to quantitative measures of reactivity, have formed the basis by which the fundamental processes underlying how this chemistry is mediated have been understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Brezicki et al also observed that elevated CH 4 pressure in the stepwise processp romoted the conversion of CH 4 on CuMOR, shifting the MeOH/Cu stoichiometry from 0.3 to 0.42. [10] We have previously shown that trinuclearc opper-oxo clusters [Cu 3 (m-O) 3 ] 2 + are selectively formed, when preparing CuMOR by pH controlled ione xchange followed by activation in O 2 at 500 8C. [6a] The yields of ca.…”
mentioning
confidence: 99%
“…3 is consistent with a mechanism that involves a reduction-oxidation reaction with Cu(I) formation as fundamental to methanol formation. Increasing evidence has recently been derived to suggest that this is the dominant mechanism for conversion of methane to methanol under high activation temperature conditions, 27,30,34,35 and this mechanistic motif can be expanded to the isothermal process for Cu-MOR. 33 Fig.…”
mentioning
confidence: 99%